Pemberdayaan Masyarakat Melalui Gerakan Literasi Perdesaan di Desa Cimanggu Kabupaten Bandung Barat - Dian Herdiana; Rendi Heriyana; Reza Suhaerawan (Jurnal Pengabdian Pada Masyarakat, 2019)
ABSTRACT: COMMUNITY EMPOWERMENT THROUGH RURAL LITERACY MOVEMENT IN CIMANGGU VILLAGE, BANDUNG BARAT DISTRICT. The community in Cimanggu Village, Bandung Barat Regency has a low literacy culture. This is due to various factors starting from the factor of the village government that does not support the literacy movement aimed at policy instruments, the cultural factors of the community who regard literacy as not a necessity and the factors that come from academics who do not disseminate information about the importance of literacy. Based on the above problems, the students of Cimahi School of Public Administration (STIA Cimahi) in the community engagement service launched a program in the form of rural literacy movement. To realize this, various activities were carried out starting from visits to village governments to encourage literacy policies at the village level. Conducting counselling to the community about the importance of literacy. Conducting literacy activities in children`s play environment that encourage children to make literacy activities a necessity and culture, as well as renovating a library in the village to make it easier for the community to access literacy infrastructure in the village.